Study on meso-fracture and energy evolution law of rock under sleeve fracturing - Shanchao HU; Jinming HAN; Junhong HUANG; Lifen PING; Yafei CHENG; Zhihao GAO; Shihao GUO; Lei YANG (Meitan kexue jishu, 2024)
In order to reveal the micromechanics of rock failure mechanisms and energy transfer patterns under different confining pressures during sleeve fracturing, a PFC3D numerical model was established based on sleeve fracturing tests and expansive force measurement experiments. The discrete element method was employed for the numerical simulation of the sleeve fracturing process. In addition, by integrating acoustic emission data, the influence of varying confining pressures on the development of microcracks in rocks and the corresponding energy variations were explored. Furthermore, the mechanical mechanism for sleeve fracturing was revealed based on the principles of elasticity. The results show that : ① There is a pressure loss in the process of sleeve liquid injection. According to the pressure loss rate, the liquid injection process can be divided into three stages: filling, pressurization, and rapid pressurization. The expansion force of the sleeve exhibits a linear relationship with the injection pressure, with a correction coefficient of 0.678. ② The PFC3D numerical model effectively represents the mechanical properties and deformation failure characteristics of rocks during sleeve fracturing, where tensile failure is the predominant mode of rock fracturing. The propagation path of cracks is determined by the confining pressure, which also suppresses the generation of microcracks within the rock. As the differential stress increases, both the number and proportion of shear cracks inside the rock gradually increase. ③ Acoustic emission signals can be divided into quiescent and active periods, with the cumulative number of cracks showing a stepwise increase. The characteristics of acoustic emission exhibit a single-peak distribution under unconfined conditions and a multi-peak distribution under confined conditions, indicating the presence of multiple fracture stages. ④ The influence scope of the sleeve expansion force is limited, and the sleeve expansion force exhibits a logarithmic correlation with the circumferential tensile stress. The tangential stress increases with the increase of stress difference. When the angle φ is 45° or 135°, the shear damage inside the rock is most obvious. ⑤ The energy input into the rock decreases as the confining pressure increases under the same expansive force. Under different confining pressures, the input energy, elastic energy, and dissipation energy of rock increase sharply in different degrees, which is mainly due to the expansion of the borehole caused by the formation of macro cracks. The growth rate of dissipative energy is faster than the elastic energy, approximately 1.27 to 1.55 times that of the elastic energy.